Crystals of monosodium urate monohydrate enhance lipopolysaccharide-induced release of interleukin 1β by mononuclear cells through a caspase 1-mediated process. Issue 2 (4th April 2008) - Giamarellos-Bourboulis, E J; Mouktaroudi, M; Bodar, E; van der Ven, J; Kullberg, B-J; Netea, M G; van der Meer, J W M
Abstract : Objective: Recent studies suggest that crystals of monosodium urate (MSU), deposited in joints of patients with acute gouty arthritis, activate the NACHT domain, leucine-rich repeat and pyrin domain-containing protein (NALP)3 inflammasome. In the present study we have investigated whether production of proinflammatory cytokines by crystals was exacerbated during costimulation with Toll-like receptor (TLR) ligands. Methods: Mononuclear cells of 22 healthy donors were stimulated by various concentrations of MSU crystals in the absence or presence of lipopolysaccharide (LPS), Pam3Cys and flagellin. Production of tumour necrosis factor α (TNFα), interleukin (IL)1β and IL6, as well as the intracellular concentrations of proIL1β were measured by ELISA. mRNA transcripts of TNFα and IL1β were assessed by real-time PCR. Stimulation experiments were also performed with peripheral blood mononuclear cells (PBMCs) of one patient carrying a NALP3 mutation. Results: MSU induced a moderate release of IL1β and IL6, but not of TNFα. Urate crystals amplified IL1β production stimulated by the TLR4 ligand LPS, while no synergy was apparent for IL6 production. In addition, no synergy between urate crystals and Pam3Cys (TLR2 ligand) or flagellin (TLR5 ligand) was apparent. The synergy between urate crystals and LPS was directed at the level of the NALP3 inflammasome, as it was present only when active IL1β was measured, but not at the level of IL1 mRNA or proIL1β. The synergy between LPS and MSU crystals ceased to exist in the presence of a caspase 1 inhibitor. Conclusions: MSU crystals act in synergy with LPS for the induction of enhanced release of IL1β. Increased cleavage of proIL1β by urate-activated caspase 1 is proposed as the underlying mechanism.